Herpes simplex virus type 2 myelitis mimicking ICU-acquired weakness as a complication of meningococcal meningitis: A case report. (February 2021) - Tsutsumi, Ken; Saito, Hiroki; Kitano, Yuka; Wakatake, Haruaki; Masui, Yoshihiro; Fujitani, Shigeki
Highlights: Herpes simplex virus (HSV) is reactivated during the immunosuppression phase of sepsis. Reactivated HSV-2 myelitis can occur among critically ill patients, mimicking ICU-acquired weakness. Before making a diagnosis of ICU-acquired weakness, reactivated HSV myelitis should be excluded. Abstract: Herpes simplex virus 2 (HSV-2) is a well-known cause of neurological complications. This case study describes the first reported case of reactivated HSV-2 myelitis, which was induced by immunosuppression due to sepsis. During the treatment of meningococcal meningitis, the patient developed quadriparesis and was later diagnosed as HSV-2 myelitis, mimicking ICU-acquired weakness. The case emphasizes the importance of excluding viral myelitis before making the diagnosis of ICU-acquired weakness.